Montmorillonite grafted ethylene propylene rubber modified nylon 6 fiber and preparation method thereof

By grafting and modifying nanomontmorillonite with ethylene propylene rubber and electrospinning, montmorillonite grafting ethylene propylene rubber modified nylon 6 fibers, the problem of poor mechanical strength of nylon 6 fibers is solved. The mechanical properties and toughness of the fiber are significantly improved.

CN119265735AInactive Publication Date: 2025-01-07WUHAN YAN SHENGBIAN TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411784642.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Nylon 6 fibers are prone to brittlement at low temperatures or dry conditions, resulting in poor mechanical strength and affecting material performance.

Method used

By grafting and modifying nanomontmorillonite with ethylene propylene rubber and electrospinned with nylon 6, montmorillonite grafted ethylene propylene rubber modified nylon 6 fibers are formed, and the nano-sized montmorillonite is used to graft the ethylene propylene rubber modified nylon 6 fibers are used. The soil and chemical bonds are connected to the rubber to avoid agglomeration and enhance the mechanical properties of the fiber.

Benefits of technology

The mechanical strength and toughness of nylon 6 fibers are effectively improved, and the elastic and impact properties are enhanced through block copolymerization structure and island-type microstructure, and the mechanical properties of composite fibers are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of nylon, and discloses a preparation method of montmorillonite grafted ethylene propylene rubber modified nylon 6 fiber, amino modified nano montmorillonite and isocyanate modified ethylene propylene rubber are subjected to a reaction, polyethylene glycol modified nylon 6 and montmorillonite grafted ethylene propylene rubber are mixed through an electrostatic spinning method, and the montmorillonite grafted ethylene propylene rubber modified nylon 6 fiber is obtained. Nano-montmorillonite is connected to ethylene-propylene rubber through chemical bonds, so that agglomeration of the nano-montmorillonite is avoided, stress concentration effect generated when the nano-montmorillonite is impacted by external force is avoided, a nylon 6 matrix is stimulated to generate microcracks, and a large amount of impact energy is consumed. The ethylene-propylene rubber has a sea-island microstructure, so that crazing can be inhibited when the ethylene-propylene rubber is impacted by external force, matrix breakage is avoided, and the mechanical property of the mixed composite fiber material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nylon, in particular to a montmorillonite-grafted EPDM rubber-modified nylon 6 fiber and a preparation method thereof. Background Art

[0002] Nylon 6, also known as polyamide 6, is obtained by the ring-opening polymerization of caprolactam. The consumption of nylon 6 ranks first among the five major engineering plastics. Nylon 6 fiber has excellent performance. It has the corrosion resistance, high temperature resistance, mildew resistance and low moisture absorption rate of general synthetic fibers. It also has the advantages of high breaking strength, light weight, good resilience and strong wear resistance. It is widely used in clothing fibers, and has a wide range of applications in sportswear, bodybuilding clothes and socks. Nylon 6 fiber is prone to brittleness at low temperature or dry conditions, which affects the performance of the material. Improving the impact strength of nylon 6 fiber and enhancing its toughness have high research value.

[0003] Chinese patent CN106751782B discloses a nylon 6 material with high heat resistance and high toughness. The heat resistance, impact and elongation toughness of nylon 6 are improved by adding nano-montmorillonite and a toughening system, which greatly expands its application field. Nano-montmorillonite has the characteristics of wide sources and low prices. At the same time, due to the nano-size effect, it has excellent mechanical properties. When added to nylon 6 fiber, it can well improve the mechanical properties of nylon fiber 6. However, when a single inorganic nanomaterial is added to the nylon 6 matrix, it is easy to agglomerate, and the toughening effect is limited. By adding the elastomer EPDM rubber, the problem of montmorillonite agglomeration can be well improved, and the resulting composite fiber material has excellent mechanical properties. Summary of the invention

[0004] 1. Technical issues to be resolved In view of the shortcomings of the prior art, the present invention provides a montmorillonite-grafted EPDM rubber-modified nylon 6 fiber and a preparation method, which solves the problem of poor mechanical strength of nylon 6 fiber fabrics.

[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a montmorillonite-grafted EPDM rubber-modified nylon 6 fiber, the montmorillonite-grafted EPDM rubber-modified nylon 6 fiber and the preparation method are as follows: (1) Mixing deionized water solvent, nano-montmorillonite, urea and sodium hydroxide, and reacting at 70-90° C. for 12-24 hours. After the reaction is completed, amino-modified montmorillonite is obtained; (2) After uniformly mixing ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and EPDM rubber, the mixture is transferred to a torque mixer for reaction. After the reaction is completed, isocyanate-modified EPDM rubber is obtained; (3) After the tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite are stirred and mixed evenly, the mixture is reacted at 45-65° C. for 8-15 hours in a nitrogen atmosphere. After the reaction is completed, montmorillonite-grafted EPDM rubber is obtained; (4) After caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate are stirred and mixed evenly, the mixture is reacted in a nitrogen atmosphere. After the reaction is completed, polyethylene glycol-modified nylon 6 is obtained; (5) After the formic acid solvent, the m-cresol solvent, the polyethylene glycol-modified nylon 6 and the montmorillonite-grafted EPDM rubber are stirred and evenly mixed, electrospinning is performed at a speed of 0.2-0.6 mL / h and a voltage of 12-24 kV. After the electrospinning is completed, the montmorillonite-grafted EPDM rubber-modified nylon 6 fiber is obtained.

[0006] Preferably, in step (1), the mass ratio of deionized water, nano-montmorillonite, urea and sodium hydroxide is 4500-9500:100:120-250:15-30.

[0007] Preferably, in step (2), the mass ratio of ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and EPDM rubber is 80-150:80-400:4-6:100.

[0008] Preferably, the reaction temperature in step (2) is 170-190° C., and the reaction time is 12-20 min.

[0009] Preferably, in step (3), the mass ratio of tetrahydrofuran, isocyanate-modified EPDM rubber and amino-modified montmorillonite is 2500-6500:100:15-40.

[0010] Preferably, in step (4), the mass ratio of caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate is 100:10-20:25-50:2-8.

[0011] Preferably, the reaction temperature in step (4) is 200-220° C., and the reaction time is 6-12 h.

[0012] Preferably, in step (5), the mass ratio of formic acid, m-cresol, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber is 120-180:180-300:100:10-30.

[0013] 3. Beneficial technical effects Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a montmorillonite-grafted EPDM rubber modified nylon 6 fiber. In the synthesis process, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) is used as an initiator and isocyanate ethyl acrylate is used as a grafting monomer to perform free radical grafting of functional groups on EPDM rubber to obtain isocyanate-modified EPDM rubber. The amino groups on amino-modified nano-montmorillonite react with the isocyanate groups on the isocyanate-modified EPDM rubber to obtain the montmorillonite-grafted EPDM rubber. Caprolactam is used as a raw material and 6-aminocaproic acid is used as a ring-opening agent to obtain nylon 6 through in-situ polymerization. Under the action of a catalyst, tetrabutyl titanate, hydroxyl groups and carboxyl groups on polyethylene glycol react to obtain polyethylene glycol-modified nylon 6. The polyethylene glycol-modified nylon 6 and the montmorillonite-grafted EPDM rubber are uniformly mixed through an electrostatic spinning method to obtain the montmorillonite-grafted EPDM rubber modified nylon 6 fiber.

[0014] The invention discloses a montmorillonite grafted EPDM rubber modified nylon 6 fiber. The nano-montmorillonite has excellent mechanical properties due to its nano-size. The nano-montmorillonite is connected to the EPDM rubber through chemical bonds, which effectively avoids the agglomeration of the nano-montmorillonite and can be evenly dispersed in the nylon 6 fiber matrix. When subjected to external force impact, a stress concentration effect is generated, thereby stimulating micro cracks in the nylon 6 matrix and inducing stress yielding in the matrix, thereby consuming a large amount of impact energy. The long flexible chain of polyethylene glycol is copolymerized in the matrix to form a block structure, which can greatly improve the mechanical properties of the matrix. The isocyanate group on the modified EPDM rubber can react with the amino group and the hydroxyl group on the nylon 6 and be evenly dispersed in the nylon 6 matrix. In the body, the EPDM rubber has an island-type microstructure, excellent elasticity, and good toughness. When subjected to external force impact, it can suppress silver streaks, thereby avoiding matrix fracture. The mechanical properties of the mixed composite fiber material are greatly improved. With the increase in the amount of toughening agent montmorillonite grafted EPDM rubber added in the embodiment, the mechanical strength of the matrix nylon fiber shows an increasing trend. When added to a certain extent, the growth trend becomes gradually slow, but there is still an obvious effect of improving the mechanical strength. In Comparative Example 1, since the elastomer EPDM rubber is not added, the single inorganic nanomaterial will agglomerate, and the matrix is ​​not modified, the mechanical strength of the obtained nylon fiber has a significant decreasing trend. DETAILED DESCRIPTION

[0015] To achieve the above object, the present invention provides the following specific implementation methods and examples: A method for preparing montmorillonite-grafted EPDM rubber-modified nylon 6 fiber is as follows: (1) Add deionized water solvent, nano-montmorillonite, urea and sodium hydroxide in a mass ratio of 4500-9500:100:120-250:15-30 to a reaction container in sequence, stir and mix, and react at 70-90° C. for 12-24 hours. After the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified montmorillonite; (2) Adding isocyanate ethyl acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and ethylene propylene rubber in a mass ratio of 80-150:80-400:4-6:100 to a reaction container in sequence, stirring and mixing evenly, transferring to a torque mixer, reacting at 170-190° C. for 12-20 minutes, and after the reaction is completed, washing with xylene and acetone, filtering, and drying to obtain isocyanate-modified ethylene propylene rubber; (3) Add tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite in a mass ratio of 2500-6500:100:15-40 to a reaction container, stir and mix them evenly, and react them at 45-65° C. for 8-15 hours in a nitrogen atmosphere. After the reaction is completed, filter, wash with acetone, and dry to obtain montmorillonite-grafted EPDM rubber; (4) adding caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate in a mass ratio of 100:10-20:25-50:2-8 into a reaction container in sequence, stirring evenly, reacting at 200-220° C. for 6-12 hours in a nitrogen atmosphere, and washing with deionized water, filtering and drying to obtain polyethylene glycol-modified nylon 6 after the reaction is completed; (5) Adding formic acid solvent, m-cresol solvent, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber in a mass ratio of 120-180:180-300:100:10-30 into a reaction container in sequence, stirring and mixing them evenly, and then performing electrospinning. The electrospinning speed is 0.2-0.6 mL / h and the voltage is 12-24 kV. After the electrospinning is completed, montmorillonite-grafted EPDM rubber-modified nylon 6 fibers are obtained.

[0016] Example 1

[0017] (1) Add deionized water solvent, nano-montmorillonite, urea and sodium hydroxide in a mass ratio of 4500:100:120:15 into a reaction container, stir and mix, and react at 70° C. for 12 hours. After the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified montmorillonite; (2) Adding ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and ethylene propylene rubber in a mass ratio of 80:80:4:100 to a reaction container in sequence, stirring and mixing evenly, transferring to a torque mixer, reacting at 170° C. for 12 minutes, and after the reaction is completed, washing with xylene and acetone, filtering, and drying to obtain isocyanate-modified ethylene propylene rubber; (3) Adding tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite in a mass ratio of 2500:100:15 into a reaction container, stirring and mixing evenly, reacting at 45°C for 8 hours in a nitrogen atmosphere, filtering after the reaction, washing with acetone, and drying to obtain montmorillonite-grafted EPDM rubber; (4) caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate in a mass ratio of 100:10:25:2 were added to a reaction container in sequence, and after being stirred evenly, the mixture was reacted at 200° C. for 6 h in a nitrogen atmosphere. After the reaction was completed, the mixture was washed with deionized water, filtered and dried to obtain polyethylene glycol-modified nylon 6; (5) Formic acid solvent, m-cresol solvent, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber in a mass ratio of 120:180:100:10 were added to a reaction container in sequence, and after being stirred and mixed evenly, electrospinning was performed at a speed of 0.2 mL / h and a voltage of 12 kV. After the electrospinning was completed, montmorillonite-grafted EPDM rubber-modified nylon 6 fibers were obtained.

[0018] Example 2

[0019] (1) Add deionized water solvent, nano-montmorillonite, urea and sodium hydroxide in a mass ratio of 5800:100:160:18 into a reaction container in sequence, stir and mix, and react at 75° C. for 15 hours. After the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified montmorillonite; (2) Adding ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and ethylene propylene rubber in a mass ratio of 90:150:4.5:100 to a reaction container in sequence, stirring and mixing evenly, transferring to a torque mixer, reacting at 175°C for 14 minutes, and after the reaction is completed, washing with xylene and acetone, filtering, and drying to obtain isocyanate-modified ethylene propylene rubber; (3) Adding tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite in a mass ratio of 3500:100:22 into a reaction container, stirring and mixing evenly, reacting at 50° C. for 9 h in a nitrogen atmosphere, filtering, washing with acetone and drying to obtain montmorillonite-grafted EPDM rubber; (4) caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate in a mass ratio of 100:12:32:3.5 are added to a reaction container in sequence, stirred evenly, and reacted at 205°C for 8 hours in a nitrogen atmosphere. After the reaction is completed, the mixture is washed with deionized water, filtered and dried to obtain polyethylene glycol-modified nylon 6; (5) Formic acid solvent, m-cresol solvent, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber in a mass ratio of 135:200:100:15 were added to a reaction container in sequence, and after being stirred and mixed evenly, electrospinning was performed at a speed of 0.3 mL / h and a voltage of 15 kV. After the electrospinning was completed, montmorillonite-grafted EPDM rubber-modified nylon 6 fibers were obtained.

[0020] Example 3

[0021] (1) Add deionized water solvent, nano-montmorillonite, urea and sodium hydroxide in a mass ratio of 7000:100:190:24 into a reaction container, stir and mix, and react at 80° C. for 18 hours. After the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified montmorillonite; (2) Adding ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and ethylene propylene rubber in a mass ratio of 115:280:5:100 to a reaction container in sequence, stirring and mixing evenly, transferring to a torque mixer, reacting at 180° C. for 16 minutes, and after the reaction is completed, washing with xylene and acetone, filtering, and drying to obtain isocyanate-modified ethylene propylene rubber; (3) Adding tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite in a mass ratio of 4500:100:28 into a reaction container, stirring and mixing evenly, reacting at 55° C. for 10 h in a nitrogen atmosphere, filtering, washing with acetone and drying to obtain montmorillonite-grafted EPDM rubber; (4) caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate in a mass ratio of 100:15:38:5 were added to a reaction container in sequence, stirred evenly, and reacted at 210° C. for 9 h in a nitrogen atmosphere. After the reaction was completed, the mixture was washed with deionized water, filtered and dried to obtain polyethylene glycol-modified nylon 6; (5) Formic acid solvent, m-cresol solvent, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber in a mass ratio of 150:235:100:20 were added to a reaction container in sequence, and after being stirred and mixed evenly, electrospinning was performed at a speed of 0.4 mL / h and a voltage of 18 kV. After the electrospinning was completed, montmorillonite-grafted EPDM rubber-modified nylon 6 fibers were obtained.

[0022] Example 4

[0023] (1) deionized water solvent, nano-montmorillonite, urea and sodium hydroxide in a mass ratio of 8200:100:220:28 were added to a reaction container in sequence, the mixture was stirred and reacted at 85° C. for 20 h. After the reaction was completed, the mixture was washed with deionized water and ethanol and dried to obtain amino-modified montmorillonite; (2) Adding ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and ethylene propylene rubber in a mass ratio of 135:350:5.5:100 to a reaction container in sequence, stirring and mixing evenly, transferring to a torque mixer, reacting at 185° C. for 18 minutes, and after the reaction is completed, washing with xylene and acetone, filtering, and drying to obtain isocyanate-modified ethylene propylene rubber; (3) Add tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite in a mass ratio of 5500:100:35 to a reaction container, stir and mix evenly, and react at 60°C for 12 hours in a nitrogen atmosphere. After the reaction is completed, filter, wash with acetone, and dry to obtain montmorillonite-grafted EPDM rubber; (4) caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate in a mass ratio of 100:18:45:6.5 are added to a reaction container in sequence, stirred evenly, and reacted at 215° C. for 10 h in a nitrogen atmosphere. After the reaction is completed, the mixture is washed with deionized water, filtered and dried to obtain polyethylene glycol-modified nylon 6; (5) Formic acid solvent, m-cresol solvent, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber in a mass ratio of 165:270:100:25 were added to a reaction container in sequence, and after being stirred and mixed evenly, electrospinning was performed at a speed of 0.5 mL / h and a voltage of 20 kV. After the electrospinning was completed, montmorillonite-grafted EPDM rubber-modified nylon 6 fibers were obtained.

[0024] Example 5

[0025] (1) Add deionized water solvent, nano-montmorillonite, urea and sodium hydroxide in a mass ratio of 9500:100:250:30 into a reaction container in sequence, stir and mix, and react at 90° C. for 24 hours. After the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified montmorillonite; (2) Adding ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and ethylene propylene rubber in a mass ratio of 150:400:6:100 to a reaction container in sequence, stirring and mixing them evenly, transferring them to a torque mixer, and reacting them at 190° C. for 20 minutes. After the reaction is completed, washing with xylene and acetone, filtering, and drying to obtain isocyanate-modified ethylene propylene rubber; (3) Add tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite in a mass ratio of 6500:100:40 to a reaction container, stir and mix evenly, and react at 65°C for 15 hours in a nitrogen atmosphere. After the reaction is completed, filter, wash with acetone, and dry to obtain montmorillonite-grafted EPDM rubber; (4) caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate in a mass ratio of 100:20:50:8 are added to a reaction container in sequence, stirred evenly, and reacted at 220° C. for 12 h in a nitrogen atmosphere. After the reaction is completed, the mixture is washed with deionized water, filtered and dried to obtain polyethylene glycol-modified nylon 6; (5) Formic acid solvent, m-cresol solvent, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber in a mass ratio of 180:300:100:30 were added to a reaction container in sequence, and after being stirred and mixed evenly, electrospinning was performed at a speed of 0.6 mL / h and a voltage of 24 kV. After the electrospinning was completed, montmorillonite-grafted EPDM rubber-modified nylon 6 fibers were obtained.

[0026] Comparative Example 1 (1) Add deionized water solvent, nano-montmorillonite, urea and sodium hydroxide in a mass ratio of 7000:100:180:24 into a reaction container, stir and mix, and react at 80° C. for 18 hours. After the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified montmorillonite; (2) Formic acid solvent, m-cresol solvent, nylon 6 and amino-modified montmorillonite in a mass ratio of 150:240:100:20 were added to a reaction container in sequence, and after stirring and mixing evenly, electrospinning was performed at a speed of 0.4 mL / h and a voltage of 18 kV. After the electrospinning was completed, montmorillonite-modified nylon 6 fibers were obtained.

[0027] The nylon 6 fibers synthesized in the examples and comparative examples were cut into strips with a size of 80 mm×10 mm×4 mm, and the impact strength test was performed on a GX-5017 impact testing machine. The notch depth was 20% of the strip thickness. The national standard for the test was GB / T 1843-2008.

Claims

1. A montmorillonite-grafted EPDM rubber-modified nylon 6 fiber, characterized in that: The montmorillonite grafted EPDM rubber modified nylon 6 fiber and the preparation method are as follows: (1) Mixing deionized water solvent, nano-montmorillonite, urea and sodium hydroxide, and reacting at 70-90° C. for 12-24 hours. After the reaction is completed, amino-modified montmorillonite is obtained; (2) After uniformly mixing ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and EPDM rubber, the mixture is transferred to a torque mixer for reaction. After the reaction is completed, isocyanate-modified EPDM rubber is obtained; (3) After the tetrahydrofuran solvent, isocyanate-modified EPDM rubber and amino-modified montmorillonite are stirred and mixed evenly, the mixture is reacted at 45-65° C. for 8-15 hours in a nitrogen atmosphere. After the reaction is completed, montmorillonite-grafted EPDM rubber is obtained; (4) After caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate are stirred and mixed evenly, the mixture is reacted in a nitrogen atmosphere. After the reaction is completed, polyethylene glycol-modified nylon 6 is obtained; (5) After the formic acid solvent, the m-cresol solvent, the polyethylene glycol-modified nylon 6 and the montmorillonite-grafted EPDM rubber are stirred and evenly mixed, electrospinning is performed at a speed of 0.2-0.6 mL / h and a voltage of 12-24 kV. After the electrospinning is completed, the montmorillonite-grafted EPDM rubber-modified nylon 6 fiber is obtained.

2. The montmorillonite-grafted EPDM rubber-modified nylon 6 fiber according to claim 1, characterized in that: In the step (1), the mass ratio of deionized water, nano-montmorillonite, urea and sodium hydroxide is 4500-9500:100:120-250:15-30.

3. The montmorillonite-grafted EPDM rubber-modified nylon 6 fiber according to claim 1, characterized in that: In the step (2), the mass ratio of ethyl isocyanate acrylate, styrene, 2,5-dimethyl-2,5-bis(tert-butylperoxyhexane) and EPDM rubber is 80-150:80-400:4-6:

100.

4. The montmorillonite-grafted EPDM rubber-modified nylon 6 fiber according to claim 1, characterized in that: The reaction temperature in step (2) is 170-190° C., and the reaction time is 12-20 min.

5. The montmorillonite-grafted EPDM rubber-modified nylon 6 fiber according to claim 1, characterized in that: In the step (3), the mass ratio of tetrahydrofuran, isocyanate-modified ethylene propylene rubber and amino-modified montmorillonite is 2500-6500:100:15-40.

6. The montmorillonite-grafted EPDM rubber-modified nylon 6 fiber according to claim 1, characterized in that: In the step (4), the mass ratio of caprolactam, 6-aminocaproic acid, polyethylene glycol and catalyst tetrabutyl titanate is 100:10-20:25-50:2-8.

7. The montmorillonite-grafted EPDM rubber-modified nylon 6 fiber according to claim 1, characterized in that: The reaction temperature in step (4) is 200-220° C., and the reaction time is 6-12 hours.

8. The montmorillonite-grafted EPDM rubber modified nylon 6 fiber according to claim 1, characterized in that: In the step (5), the mass ratio of formic acid, m-cresol, polyethylene glycol-modified nylon 6 and montmorillonite-grafted EPDM rubber is 120-180:180-300:100:10-30.

Citation Information

Patent Citations

  • A high heat-resistant and high-toughness nylon 6 material

    CN106751782B